Data from: Challenges of NGS in conservation management: insights from long-term monitoring of corridor effects on the genetic diversity of mouse lemurs in a fragmented landscape - Montero, B. Karina; Refaly, Ernest; Ramanamanjato, Jean-Baptiste; Randriatafika, Faly; Rakotondranary, S. Jacques; Wilhelm, Kerstin; Ganzhorn, Jörg U.; Sommer, Simone (Dryad, 2018)
Long-term genetic monitoring of populations is essential for efforts aimed
at preserving genetic diversity of endangered species. Here, we employ a
framework of long-term genetic monitoring to evaluate the effects of
fragmentation and the effectiveness of the establishment of corridors in
restoring population connectivity and genetic diversity of mouse lemurs
Micocebus ganzhorni. To this end, we supplement estimates of neutral
genetic diversity with the assessment of adaptive genetic variability of
the MHC. In addition, we address the challenges of long-term genetic
monitoring of functional diversity by comparing the genotyping performance
and estimates of MHC variability generated by SSCP/Sanger-sequencing with
those obtained by high throughput sequencing (NGS, Illumina), an issue
that is particularly relevant when previous work serves as a baseline for
planning management strategies that aim to ensure the viability of a
population. We report that SSCP greatly underestimates individual
diversity and that discrepancies in estimates of MHC diversity
attributable to the comparisons of traditional and NGS genotyping
techniques can influence the conclusions drawn from conservation
management scenarios. Evidence of migration among fragments in Mandena
suggests that mouse lemurs are robust to the process of fragmentation and
that the effect of corridors is masked by ongoing gene flow. Nonetheless,
results based on a larger number of shared private alleles at neutral loci
between fragment pairs found after the establishment of corridors in
Mandena suggest that gene flow is augmented as a result of enhanced
connectivity. Our data points out that despite low effective population
size, M. ganzhorni maintains high individual heterozygosity at neutral
loci and at MHC II DRB gene and that selection plays a predominant role in
maintaining MHC diversity. These findings highlight the importance of
long-term genetic monitoring in order to disentangle between the processes
of drift and selection maintaining adaptive genetic diversity in small
populations.
EVA-2018-135-OA.R1_MHCIIDRB_1998-2016MHII DRB exon 2 genotypes of mouse
lemurs caught in the littoral forests of Mandena during two sampling
periods: 1998-2003 and 2012-2016. Data was generated using single-stranded
conformation polymorphism (SSPC) and amplicon based NGS (Illumina)
approach.EVA-2018-135-OA.R1_msats_1998-2016Microsatellite genotypes of
mouse lemurs caught in the littoral forests of Mandena during two sampling
periods: 1998-2003 and 2012-2016.
Keywords: Primates; corridors; MHC; Microcebus ganzhorni; SSCP vs NGS